Recurrence Status, Perineural Invasion, and Hypothyroidism Are Associated With Lymph Node Metastasis in Cutaneous Squamous Cell Carcinoma: A Case–Control Study. Issue 4 (1st April 2022) - Lobl, Marissa; Feinstein, Shera; Lauer, Scott; Sutton, Adam; Wysong, Ashley
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: Lymph node metastasis is a critical prognostic indicator for mortality in patients with cutaneous squamous cell carcinoma (SCC). OBJECTIVE: To identify and characterize key risk factors for SCC lymph node metastasis. METHODS: This was a multi-institutional, case–control study of 65 cutaneous SCCs with known lymph node metastasis matched with 195 cutaneous SCCs without lymph node metastasis (3:1 matching). The cases and controls were matched by anatomic location, age, and sex. Odds ratios (ORs) and their 95% confidence intervals (CIs) were generated to determine the association between specific risk factors and lymph node metastasis in a multivariate analysis. RESULTS: Recurrent tumors ( p < .001), perineural invasion ( p < .001), lymphovascular invasion ( p = .002), size of 2 cm or greater ( p = .008), and hypothyroidism ( p = .03) were significantly more common in the lymph node metastasis cohort. Recurrence (OR 6.3, 95% CI 2.6–15.3), perineural invasion (OR 4.5, 95% CI 1.7–11.8), and hypothyroidism (OR 2.7, 95% CI 1.04–7.0) remained significant on performing a multivariate analysis. CONCLUSION: Lymph node metastasis in SCC is associated with recurrence, perineural invasion, lymphovascular invasion, size of 2 cm or greater, and hypothyroidism. Clinical consideration of these findings within the context of current staging systems may help improve patient outcomes.